Generation and characterisation of adipose tissue-and umbilical-cord-derived mesenchymal stem cells expressing trail apoptotic ligand - Shamsul Kamal, Aishah Amirah (2024)
Recent studies have shown that mesenchymal stem cells (MSCs) expressing TNFRelated Apoptosis Inducing Ligand (MSC-TRAIL) can eliminate both lung cancer cells and lung cancer stem cells efficiently. Although there have been several studies on the efficacy of various sources of MSC-TRAIL on several cancers, there have been very limited studies on which sources of MSCs are the most efficient in expressing the TRAIL protein and biological properties of the engineered MSCs postmodification. The engineered MSCs utilised in previous projects have varying genetic constructs of the TRAIL-encoding lentiviruses transduced. Moreover, the period of time required for ADMSCs to achieve a similar level of protein expression to UCMSCs, was longer compared to UCMSCs in previous studies, suggesting UCMSCs having higher expression efficiency compared to ADMSCs. This raises the possibility of utilising other sources of MSCs, such as umbilical cord (UC) as a vector for TRAIL. This project aims to generate adipose tissue (AD) and umbilical cord (UC)-derived MSCs expressing TRAIL and characterise these cells post-modification. The hypothesis of this study is TRAIL-expressing MSCs can be generated from AD and UC, and these engineered cells retain the MSC characteristics. The methods utilised are explained as follows. TRAIL encoding and empty vector lentivirus (LV) were produced through the transfection of LV component plasmids into 293FT cells. The virions were concentrated to >10⁶ transducing units (TU)/mL. The MSCs were then transduced based on a range of MOIs. The TRAIL expression from the putative ADMSC-TRAIL and putative UCMSC-TRAIL was validated using ELISA. The engineered MSCs were then characterised through morphology observation, flow cytometry analysis, and differentiation assay. Analysis of transduction efficiency exhibited higher intensity of reporter gene-positive cells detected in putative UCMSCTRAIL compared to putative ADMSC-TRAIL. Significantly higher TRAIL protein was also detected in the protein lysate and conditioned medium of putative UCMSCTRAIL than putative ADMSC-TRAIL, empty vector (MSC-EV), and wild-type MSCs (MSC-WT). Moreover, all engineered MSCs retained their original characteristics post-transduction. The putative MSC-TRAIL were able to differentiate into adipocytes, osteocytes, and chondrocytes and maintained their MSC surface marker expression (CD44, CD90, CD105, and CD73). In conclusion, the TRAIL expression and characterisation analyses verified that the ADMSC-TRAIL and UCMSC-TRAIL have been generated. UCMSCs are discovered to be potentially more effective as a vector for TRAIL compared to ADMSCs. To further compare the potency of TRAILtransduced MSCs in cancer therapy, functional assays incorporating MSC-TRAIL and NSCLC cell lines can be performed in the future.